Molecular detection of Cryptosporidium as a zoonotic pathogen, in pet birds of Isfahan, Iran - Mohammad Ahmadi Gharacheh; Majid Gholami-Ahangaran; Hasan Momtaz (مجله دانشگاه علوم پزشکی گرگان, 2020)
Background and Objective: Cryptosporidium is one of protozoan parasites. Cryptosporidium is important in human public health. This parasite has many species, some of which are common in animal and human hosts. One of the animal hosts of this parasite is pet bird. This parasite causes digestive and respiratory problems in pet birds. This study was performed for molecular identification of Cryptosporidium as a zoonotic pathogen of pet birds. Methods: In this descriptive laboratory study, fecal samples of 114 cages (50 Passeriformes and 64 Psittaciforms) from all over Isfahan city in Iran were collected by collecting history and after extracting the genome; the Cryptosporidium was detected by specific primers, based on ssrRNA gene. Results: In 16.66% of the canaries with gastrointestinal symptoms and 4.54% of apparently healthy canaries the ssrRNA gene of Cryptosporidium was detected. In addition, the gene was detected in 10% of cockatiel and 4.16% of budgerigars and in other species of Psittaciforms was not detected. Conclusion: Pet birds in Isfahan can be considered as a source of Cryptosporidium infection.